Association of TCF7/L2 SNPs rs1790314 and rs12255372 Polymorphisms in Type 2 Diabetes Mellitus with Renal and Inflammatory Markers - Idoko Roseline; Brown Holy; Onwuli Donatus; Nwachuku Edna Ogechi (Asian Journal of Medicine and Health, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a persistent metabolic disorder characterised by elevated blood glucose levels and influenced by both genetic and environmental factors. Aim: This study investigated the association of TCF7L2 SNPs rs1790314 and rs12255372 with renal and inflammatory markers in type 2 diabetes mellitus. Methods: This cross-sectional study examined biochemical markers and the TCF7L2 SNPs rs12255372 and rs1790314 in 140 patients with T2DM attending the diabetic clinics of Rivers State University Teaching Hospital (RSUTH) and the University of Port Harcourt Teaching Hospital (UPTH), together with 40 non-diabetic controls. Biochemical parameters, including fasting blood glucose (FBG), HbA1c, C-peptide, insulin, HOMA-IR, cystatin C, estimated glomerular filtration rate (eGFR), creatinine, urea, and electrolytes, were measured using colourimetric and ELISA methods. The TCF7L2 variants were genotyped using BigDye Terminator sequencing. Data on these parameters and the TCF7L2 genotypes were analysed using GraphPad Prism, SPSS, and Excel. Descriptive statistics were presented as means ± SD, while inferential analyses included Student's t-test, Pearson's correlation, linear regression, and one-way ANOVA. Statistical significance was set at p < 0.05. Results: The study found an increasing prevalence of T2DM in Port Harcourt in recent years, with rates of 23% in males and 21% in females, and a glycaemic control rate of 38.75%. The TCF7L2 genotype distribution showed that 32.5% had the CC genotype and 11.25% had the CT/TT genotypes at rs1790314, whereas 41.25% had the GG genotype and 3.75% had the GT/TT genotypes at rs12255372. Abnormalities such as hyponatraemia, low chloride levels, and hyperkalaemia were observed in patients with poorly controlled T2DM. Physical activity was associated with better cardiovascular health, as indicated by lower cardiac troponin I (cTnI) levels. Standard antidiabetic drugs, including metformin (Glucophage) and sulfonylureas (Amaryl), were associated with dyslipidaemia, particularly in males, characterised by reduced HDL-C and triglyceride levels and increased atherogenic ratios such as TC/TG. An association was also found between chloride levels and the T allele at rs1790314. BMI and WHR did not correlate with the CT/TT polymorphisms at rs1790314 or the GT/TT polymorphisms at rs12255372, although both were higher in individuals with T2DM carrying the TCF7L2 variants. The rs1790314 CT/TT mutation was associated with higher triglyceride, TC/TG, and TC/HDL ratios and lower HDL-C levels. Insulin resistance, indicated by increased C-peptide levels, was observed in rs1790314 CT/TT carriers, while renal abnormalities associated with rs12255372 GT/TT correlated with cystatin C. Overall, TCF7L2 variants were associated with dyslipidaemia, elevated cystatin C, and increased C-peptide levels. Patients with mutant T alleles in both variants had significantly higher HbA1c, WHR, BMI, lipid, atherogenic marker, and troponin I levels. Conclusion: The findings suggest that increased insulin resistance and impaired cellular uptake occurred alongside significantly higher C-peptide levels in individuals with the CT/TT polymorphic variants of transcription factor 7-like 2 (TCF7L2) rs1790314. Furthermore, renal abnormalities were associated with the TCF7L2 rs12255372 GT/TT polymorphic variant, which was positively associated with cystatin C in participants with type 2 diabetes mellitus (T2DM) who expressed TCF7L2.